Organizational imaginaries : tempering capitalism and tending to communities through cooperatives and collectivist democracy - Chen, Katherine K.; Chen, Victor Tan (Emerald Publishing Limited, 2021)
Our everyday lives are structured by the rhythms, values, and practices of various organizations, including schools, workplaces, and government agencies. These experiences shape common-sense understandings of how ';best' to organize and connect with others. Today, for-profit managerial firms dominate society, even though their practices often curtail information-sharing and experimentation, engender exploitation, and exclude the interests of stakeholders, particularly workers and the general public. This 'Research in the Sociology of Organizations' volume explores an expansive array of organizational imaginaries, or conceptions of organizational possibilities, with a focus on collectivist-democratic organizations that operate in capitalist markets but place more authority and ownership in the hands of stakeholders other than shareholders. These include worker and consumer cooperatives and other enterprises that, to varying degrees Emphasize social values over profit Are owned not by shareholders but by workers, consumers, or other stakeholders Employ democratic forms of managing their operations Have social ties to the organization based on moral and emotional commitments 'Organizational Imaginaries' explores how these enterprises generate solidarity among members, network with other organizations and communities, contend with market pressures, and enhance their larger organizational ecosystems. By ensuring that organizations ultimately support and serve broader communities, collectivist-democratic organizing can move societies closer to hopeful 'what if' and 'if only' futures. This volume is essential for researchers and students seeking innovative and egalitarian approaches to business and management.
Includes index.
Keywords: Cooperative societies.; Business & Economics -- Organizational Development.; Organizational theory & behaviour.; elektronické knihy; electronic books